Antimicrobial Effect of Rosella Flower Extract (Hibiscus sabdariffa L.) Against Multispecies Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans - Vierlia Nurlailia Putri; Trijani Suwandi; Mikha Sundjojo (Universitas Muhammadiyah Yogyakarta, 2024)
Periodontal disease has a high prevalence in the world and Indonesia. There are 2 types of periodontal disease, such as gingivitis and periodontitis, which can be caused by pathogenic bacteria such as Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans. Minimizing periodontal disease can be done by brushing, flossing, scaling, and using mouthwash that contains antibacterial. Rosella (Hibiscus sabdariffa L.) is an herbal plant that contains antibacterial properties, so it can be used as an additional therapy to minimize periodontal disease. The research was conducted in the MiCore laboratory FKG Usakti with the method in this study using an in vitro laboratory experiment using a biofilm assay test with a concentration of 1 g/mL, 0.50 g/mL, 0.25 g/mL, 0.125 g/mL, 0.0625 g/mL, 0.0312 g/mL, 0.015 g/mL. The extract was distributed into well plates, stained with crystal violet, incubated for 1 hour, 6 hours, and 24 hours, and then counted using a microplate reader. The results showed that extract concentrations starting from 0.015 g/mL at an incubation period of 1 hour, concentrations starting from 0.125 g/mL at an incubation period of 6 hours, and concentrations starting from 0.0625 g/mL at an incubation period of 24 hours were proven to inhibit bacterial growth and proved to be more effective than 0.2% chlorhexidine with significantly different results (p<0.05). It can be concluded that Rosella extract can inhibit the growth of multispecies bacteria Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans.